Overhead shoulder press - In-front of the head or behind the head? - Mark R. McKean; Brendan J. Burkett (Elsevier, 2015)
Background: Using a cross-sectional design comparison, two overhead press techniques (in-front of the head or behind the head) were compared. The purpose of this study was to determine the impact of behind the head or in-front of the head overhead pressing technique on shoulder range of movement (ROM) and spine posture. The overhead press is commonly prescribed exercise. The two techniques (in-front of the head or behind the head) may influence joint mechanics and therefore require an objective analysis. Methods: Passive shoulder ROM quantified using goniometric measures, dynamic ROM utilised three-dimensional (3D) biomechanical measures (120 Hz) of 33 participants performing overhead pressing in a seated position. The timing and synchronisation of the upper limb shoulder and spine segments were quantified and influence of each technique was investigated. Results: The in-front technique commenced in lordotic position, whilst behind the head technique commenced in kyphotic position. Behind the head technique started with less thoracic extension than in-front condition. The thoracic spine remained extended and moved between 12° and 15° regardless of gender or technique. The techniques resulted in a significant difference between genders. Males were able to maintain a flat or normal lumbar lordosis, whereas females tended to kyphotic. Conclusion: Shoulder ROM was within passive ROM for all measures except external rotation for males with the behind the head technique. To avoid possible injury passive ROM should be increased prior to behind the head protocol. Females showed greater spine movements, suggesting trunk strengthening may assist overhead pressing techniques. For participants with normal trunk stability and ideal shoulder ROM, overhead pressing is a safe exercise (for the shoulder and spine) when performed either in-front of or behind the head.